1985
DOI: 10.1002/1097-0142(19850901)56:5<991::aid-cncr2820560503>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia-induced vascular injury in normal and neoplastic tissue

Abstract: The sequential morphologic alterations in normal skeletal muscle in rats, Walker 256 tumors in rats, and transmissible venereal tumors (TVT) in dogs following microwave-induced hyperthermia (43 degrees C and 45 degrees C for 20 minutes), were studied by histologic and ultrastructural examination. Normal muscle and Walker 256 tumors showed edema, congestion, and hemorrhage at 5 minutes post-heating (PH), followed by suppuration, macrophage infiltration, and thrombosis at 6 and 48 hours PH, and finally by regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…The results in the present study indicate that SNP infusion should not be given if muscle temperatures above 43.08C are measured during HT, to avoid a further increase in muscle temperature. At this temperature, there is an imminent danger of muscle necrosis, even without the use of SNP, as shown in experiment F. This ®nding is in accordance with what has been reported by Badylak et al 17 , who found necrosis of skeletal muscle after microwave-induced HT at 438C for 30 min.…”
Section: Discussionsupporting
confidence: 92%
“…The results in the present study indicate that SNP infusion should not be given if muscle temperatures above 43.08C are measured during HT, to avoid a further increase in muscle temperature. At this temperature, there is an imminent danger of muscle necrosis, even without the use of SNP, as shown in experiment F. This ®nding is in accordance with what has been reported by Badylak et al 17 , who found necrosis of skeletal muscle after microwave-induced HT at 438C for 30 min.…”
Section: Discussionsupporting
confidence: 92%
“…As an example, Coleman et al [ 10 ] studied regional hyperthermia in which the tumour tissue has been heated to keep its temperature above 42°C for a few hours. However, among the concurrent treatments of cancer, hyperthermia seems to be the less developed in the clinical practice [ 11 13 ]. One reason may be the difficulty of targeting sufficient amounts of heat to the tumour tissue only.…”
Section: Introductionmentioning
confidence: 99%
“…Two sessions of hyperthermia at 43°C or 45°C for implanted tumors in rats caused no change in the temperature of the surrounding normal tissue but did induce an increase in the intratumoral steady‐state temperature. These two sessions of hyperthermia caused thrombosis in 90% of the intratumoral tissue 21…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxic and necrotic areas in the tumor may be increased relative to prehyperthermia, and midtherapy CT studies showed a statistically significant reduction in ΔCT max in CR patients. As shown by histologic changes due to hyperthermia in experimental and human tumors, vascular damage is prominent in the tumor center, whereas damage to the surrounding normal tissue is small 21–23. This suggests that the issue of hypoxic cells may not be critical.…”
Section: Discussionmentioning
confidence: 99%